Asymptomatic migration of ventral mesh for incisional hernia into the small intestine: A case report. Issue 7 (29th May 2019) - Triantafyllou, Evangelia; Anastasiadis, Iraklis; Konstantinidis, Dimitrios; Syllaios, Athanasios; Gerovasileiou, Efrosyni; Tsiripidis, Orestis
Abstract: Even though mesh migration is a rare complication, it must be considered in the differential diagnosis when investigating abdominal pain and digestive complications in patients with history of abdominal operations. Abstract : Even though mesh migration is a rare complication, it must be considered in the differential diagnosis when investigating abdominal pain and digestive complications in patients with history of abdominal operations.